2008
DOI: 10.1186/1471-213x-8-30
|View full text |Cite
|
Sign up to set email alerts
|

Teneurin-1 is expressed in interconnected regions of the developing brain and is processed in vivo

Abstract: Background: Teneurins are a unique family of transmembrane proteins conserved from C. elegans and D. melanogaster to mammals. In vertebrates there are four paralogs (teneurin-1 to -4), all of which are expressed prominently in the developing central nervous system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
76
0
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(89 citation statements)
references
References 42 publications
6
76
0
7
Order By: Relevance
“…We previously used antisera raised against the ICD and EGFlike repeats of teneurin-1 on immunoblots of embryonic chicken brain (Kenzelmann et al 2008). The anti-teneurin-1 ICD antibodies recognized a band running at approximately 64kDa, and the antiserum directed to the EGF-like repeats of teneurin-1 recognized larger bands corresponding to the full length protein.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We previously used antisera raised against the ICD and EGFlike repeats of teneurin-1 on immunoblots of embryonic chicken brain (Kenzelmann et al 2008). The anti-teneurin-1 ICD antibodies recognized a band running at approximately 64kDa, and the antiserum directed to the EGF-like repeats of teneurin-1 recognized larger bands corresponding to the full length protein.…”
Section: Discussionmentioning
confidence: 99%
“…The nucleus mesencephalicus lateralis pars dorsalis is also labeled. In the E17 cerebellum, which is a prominent site of expression for other teneurins (e.g., Kenzelmann et al 2008), teneurin-4 immunostaining is faint (not shown). This corresponds with the faint band seen in homogenates of the E17 cerebellum (Fig.…”
Section: Immunolocalization Of Teneurin-4 In the Chick Embryomentioning
confidence: 99%
See 3 more Smart Citations